Exploring teachers’ perception of classroom environment in improving students' achievement in primary school. - Ismail, Zaharah; Ahmad, Nor Aniza; Sulong, Rose Manisah (Journal of Islamic, Social, Economics and Development, 2025)
This study aims to explore teachers' perceptions of how the classroom environment influences the achievement of primary school students. According to data released by the Ministry of Education, 13% of students have not yet reached the minimum proficiency level, which is concerning and calls for intervention to reduce this percentage. Given that student achievement, particularly literacy, is the focus of this study, the classroom environment is believed to impact students' learning experiences. The classroom environment includes elements such as layout, class size, and psychosocial dynamics that enhance student motivation and engagement. This qualitative study seeks to gain in-depth insights into this situation. The findings indicate that all dimensions of the classroom environment affect student achievement, underscoring the need for efforts to improve resources and comfort within the classroom setting